Intramedullary nailing of femoral shaft fractures in adults. Issue 2 (April 2017) - Memarzadeh, Arman; Tissingh, Elizabeth Khadija; Hull, Peter; Trompeter, Alex
Abstract: Diaphyseal femoral fractures are common and can present as isolated injuries or as part of a polytrauma situation. Management of these fractures requires an understanding of the timing of definitive surgery in systemically unwell patients, as well as the physiologic effects of reaming and instrumentation of the femoral canal. An appreciation of biomechanics of femoral nails, along with other implants, and the nuances of their application is essential in achieving a satisfactory outcome.